China's R&D subsidies: Allocation and effectiveness - Philipp Boeing (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
This study investigates the allocation of China's R&D subsidies and its effectiveness in stimulating firms' own R&D investments for the population of Chinese listed firms throughout the time period 2001 to 2006. For allocation, we find that firm participation is determined by prior grants, high quality inventions, and minority state-ownership. Provincial variation in China's transition towards a market-driven economy reveals that R&D subsidies are less often distributed by more market-oriented provincial governments and that China's innovation policy is more supportive of firms located in developed provinces. Considering effectiveness, we find that grants instantaneously crowd-out firms' own R&D investments but are neutral in later periods. In 2006, one public RMB reduces own R&D investments made by firms by half a RMB. For repeated recipients, high-tech firms, and minority state-owned firms grants have an insignificant effect.
urn:nbn:de:bsz:180-madoc-374040
Keywords: O38; O32; 330; R&D subsidies; economic transition; China; propensity score matching; difference-in-differences